2017
DOI: 10.1088/1751-8121/aa8a10
|View full text |Cite
|
Sign up to set email alerts
|

Irreversibility of the renormalization group flow in non-unitary quantum field theory

Abstract: We show irreversibility of the renormalization group flow in non-unitary but PT -invariant quantum field theory in two space-time dimensions. In addition to unbroken PT -symmetry and a positive energy spectrum, we assume standard properties of quantum field theory including a local energy-momentum tensor and relativistic invariance. This generalizes Zamolodchikov's ctheorem to PT -symmetric hamiltonians. Our proof follows closely Zamolodchikov's arguments. We show that a function c eff (s) of the renormalizati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 70 publications
1
24
0
Order By: Relevance
“…Still, we should point out that our non-unitary 4D theories described above have an avatar of 2D unitarity: a modified notion of reflection positivity exists in our theories. Related 2D constructions have played a role in recent work on non-unitary extensions of Zamolodchikov's c-theorem [42]. Such structures, involving "hidden" unitarity, may also shed more light on the question of which non-unitary theories in 2D are able to encode the unitary 4D physics in the original construction of [2].…”
Section: Discussionmentioning
confidence: 99%
“…Still, we should point out that our non-unitary 4D theories described above have an avatar of 2D unitarity: a modified notion of reflection positivity exists in our theories. Related 2D constructions have played a role in recent work on non-unitary extensions of Zamolodchikov's c-theorem [42]. Such structures, involving "hidden" unitarity, may also shed more light on the question of which non-unitary theories in 2D are able to encode the unitary 4D physics in the original construction of [2].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, m corresponds to the number of times the link wraps the longitude of the torus and n corresponds to the number of times the link wraps the meridian. 43 The links may be characterized by the components that make it up. In particular, we have…”
Section: Torus Links and Canonical Wordsmentioning
confidence: 99%
“…An other example in [53] terminates in a flow from the Yang-Lee edge singularity to the trivial c = 0 theory. Recently in [54] it was shown that it is possible to relax the requirement of unitary and still show the existence of a monotonic decreasing c-function along such flows. So the learning here is that it is not a manifest impossibility to conceive an RG flow between a non-unitary UV CFT and a unitary IR CFT.…”
Section: The Rg Behaviour When Not Restricted To the Integrable Locusmentioning
confidence: 99%